Moisture-curable adhesive composition

By using a combination of high content of wet hardenable resin and modified polyesterene resin in wet hardenable adhesive, the problem of insufficient adhesion on polyesterene substrates is solved, and the adhesive is thickened or gelled in a short time is achieved. It is suitable for bonding applications of various substrates.

JP7666331B2Active Publication Date: 2025-04-22TOYOBO MC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021567647
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-27
Filing Date
2020-12-24
Publication Date
2025-04-22
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

It is difficult for existing wet hardenable adhesives to achieve good adhesion on polyester alkenes, and it is also very difficult to increase the viscosity or gelation of the adhesive in a short time.

Method used

Using a combination of a high-content wet hardenable resin and a modified polyesterene resin, the mutual solubility and compatibility of the resin are enhanced by introducing polyethyl ether or (formalic acid ester polymer into the polyesterene resin, and laser polymerizable monomer, polymerizer and silanol condensation catalyst are added to achieve effective hardening of the adhesive.

Benefits of technology

Adhesives with high adhesion and good fluidity on polyester alkenes are achieved, which can quickly thicken or gelatinize under appropriate conditions, and are suitable for bonding and sealing materials of a variety of substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666331000001
    Figure 0007666331000001
  • Figure 0007666331000002
    Figure 0007666331000002
  • Figure 0007666331000003
    Figure 0007666331000003
Patent Text Reader

Abstract

A moisture-curable adhesive resin composition containing a moisture-curing resin (A) and a modified polyolefin resin (B), the content of the modified polyolefin resin (B) being 2 parts by mass or more with respect to 100 parts by mass of the moisture-curing resin (A). Provided is an adhesive composition containing a moisture-curing resin and a modified polyolefin, the adhesive composition having good liquidity and good adhesion to a polyolefin resin substrate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a moisture-curable adhesive composition that has excellent adhesion to polyolefin substrates. [Background technology]

[0002] Conventionally, curing adhesives such as room temperature curing adhesives and heat curing adhesives have been used as adhesives for bonding adherends together. In recent years, organic polymers having reactive silyl groups have been used extensively as moisture curing adhesives, because the silyl groups undergo hydrolysis or other reactions due to moisture in the air at room temperature, and crosslinking occurs through the formed siloxane bonds. However, strong adhesion to polyolefin substrates such as polyolefin plates, polyolefin sheets, and polyolefin films has not been achieved, and development has been desired.

[0003] Under these circumstances, several moisture-curable adhesive compositions with improved adhesion to polyolefin substrates have been proposed, such as a composition (see Patent Document 1) in which a polyether resin having a hydrolyzable silyl group and a vinyl resin having a hydrolyzable silyl group are blended with a curing catalyst, a styrene-based tackifier, a reactive diluent, and a chlorinated polyolefin resin.

[0004] [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 5922985 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the inventors' investigations revealed that the proposed moisture-curing adhesive is insufficient in terms of adhesion to polyolefin substrates because the compatibility and solubility of the resin having a hydrolyzable silyl group with the chlorinated polyolefin is poor, and therefore the amount of the chlorinated polyolefin resin cannot be increased. Furthermore, even if the adhesion to polyolefin substrates is greatly improved, it is extremely difficult to obtain a moisture-curing adhesive composition that has a liquid state within a range that can be used as an adhesive, such as an increase in viscosity or gelation of the adhesive over a short period of time.

[0007] The present invention has been made in consideration of the above-mentioned problems in the conventional art. As a result of extensive research by the inventors into moisture-curing adhesives that have excellent adhesion to polyolefin resin substrates, they have discovered that an adhesive composition containing a high proportion of a moisture-curing resin and a modified polyolefin resin has both adhesion to polyolefin substrates and dissimilar substrates and is liquid, and have thus completed the present invention.

[0008] That is, an object of the present invention is to provide a moisture-curable adhesive composition which has both adhesion to polyolefin substrates and dissimilar substrates and is in a liquid state that can be substantially used as an adhesive. [Means for solving the problem]

[0009] In order to achieve the above object, the following invention has been made.

[0010] A moisture-curing adhesive resin composition comprising a moisture-curing resin (A) and a modified polyolefin resin (B), wherein the amount of (B) is 2 parts by mass or more per 100 parts by mass of (A).

[0011] The moisture-curable adhesive composition as described above, wherein the moisture-curable resin (A) is a resin containing a hydrolyzable silyl group at the terminal and having a main chain made of a polyether or a (meth)acrylate.

[0012] The moisture-curable adhesive composition as described above, wherein the modified polyolefin resin (B) is a polyether resin or a (meth)acrylate polymer grafted via an amide bond and / or an ester bond, and the main chain is a polyolefin resin.

[0013] Preferably, in the adhesive resin composition, the graft amount of the polyether resin and the (meth)acrylate polymer in the modified polyolefin resin (B) is 2 to 40 mass %.

[0014] Preferably, in the adhesive resin composition, the modified polyolefin resin (B) has a molecular weight of 10,000 to 150,000.

[0015] In a more preferred embodiment, the moisture-curable adhesive resin composition further contains a radical polymerizable monomer (C) having a (meth)acryloyl group at its terminal, and further contains a radical polymerization initiator (D) and a silanol condensation catalyst (E). Effect of the Invention

[0016] When the moisture-curable composition of the present invention is used as an adhesive, it becomes possible to achieve both sufficient adhesion to polyolefin substrates and a liquid state within a range that allows practical use as an adhesive. BEST MODE FOR CARRYING OUT THEINVENTION

[0017] Hereinafter, an embodiment of the present invention will be described in detail.

[0018] <Moisture-curing resin (A)> The moisture-curable resin (A) used in the present invention is a resin that exhibits the property that the silyl group undergoes hydrolysis reaction or the like due to moisture in the air at room temperature, and crosslinks through the formed siloxane bond. Although not limited thereto, examples thereof include resins containing hydrolyzable silyl groups, and resins containing hydrolyzable silyl groups and having an olefin content of 50 mass% or less can be suitably used, and more specifically, examples thereof include polyether resins having hydrolyzable silyl groups, (meth)acrylate-based (co)polymers having hydrolyzable silyl groups, etc. These may be used alone or in combination of two or more kinds.

[0019] Examples of the resin containing a hydrolyzable silyl group include vinyl polymers or polyether resins having a hydrolyzable silyl group, such as ethylene polymers, propylene polymers, isobutylene polymers, acrylate polymers, methacrylate polymers, styrene polymers, vinyl chloride polymers, vinylidene chloride polymers, butadiene polymers, isoprene polymers, vinyl acetate polymers, vinyl alcohol polymers, vinyl butyral polymers, and vinyl ether polymers. Copolymers containing these polymers may also be used.

[0020] A hydrolyzable silyl group is a group that has a hydroxyl group or a hydrolyzable group bonded to a silicon atom and can crosslink by forming a siloxane bond through a reaction accelerated by a silanol condensation catalyst. The hydrolyzable silyl group is represented by the following general formula (1). (1) -SiR 1 (3-n) X n (n=1-3, R 1 represents an alkyl group, an aryl group, or an aralkyl group having 1 to 20 carbon atoms, and X represents a hydrolyzable group.

[0021] Examples of the hydrolyzable group X in the above general formula (1) include a hydrogen group, a hydroxyl group, a halogen atom such as a chlorine atom, an alkoxy group such as a methoxy group, an ethoxy group, or a propoxy group, an acyloxy group, an amino group, an amido group, a mercapto group, an alkenyloxy group, an aminooxy group, and a ketoximate group. From the viewpoint of handleability based on hydrolysis, an alkoxy group is preferred.

[0022] The polyether resin having a hydrolyzable silyl group is represented by the general formula -R 2 -O-(wherein, R 2 is a straight-chain or branched alkylene group having 1 to 15 carbon atoms.) and it is preferable that the repeating unit is the main chain. 2 In the formula -O-, R 2 is preferably a linear or branched alkylene group having 2 to 8 carbon atoms, and more preferably an alkylene group having 2 to 4 carbon atoms. In addition, it is preferable that the main chain has a hydrolyzable silyl group (1), more preferably that the main chain has a hydrolyzable silyl group at least at one end, and a polyether resin having a functional group represented by general formula (A) at least at one end of the main chain is preferred. General formula (A)

[0023] [ka] (In the formula, R 3 is a monovalent hydrocarbon group having 1 to 12 carbon atoms, R 4 is a monovalent hydrocarbon group having 1 to 6 carbon atoms, and n is an integer of 0 to 2.

[0024] As the (meth)acrylate-based (co)polymer having a hydrolyzable silyl group, a (meth)acrylate-based (co)polymer whose main chain contains a repeating unit of a (meth)acryloyl group and has a functional group represented by the above general formula (A) at least at one end of the main chain or in a side chain is preferred.

[0025] Examples of (meth)acrylate monomers for obtaining (meth)acrylate-based (co)polymers having a hydrolyzable silyl group include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, isooctyl (meth)acrylate, neopentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, p) (meth)acrylic acid alkyl esters such as isooctyl acrylate, isodecyl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, and lauryl (meth)acrylate; (meth)acrylic acid alicyclic alkyl esters such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and adamantyl (meth)acrylate; 2-hydroxyethyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxybutyl (meth)acrylate, and (meth)acrylic acid. Examples of the acrylates include hydroxypropyl acrylate, hydroxyethyl (meth)acrylate and ε-caprolactone addition reaction products, phthalic acid monohydroxyethyl acrylate, 2-hydroxy-3-phenoxypropyl acrylate and other hydroxy group-containing (meth)acrylic acid esters, aromatic ring-containing (meth)acrylic acid esters, such as benzyl acrylate, benzyl methacrylate, 2-phenoxyethyl (meth)acrylate, and other 2-methoxyethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate and other heteroatom-containing (meth)acrylic acid esters, ethoxylated phenol acrylate, ethoxylated paracumylphenol acrylate, ethoxylated nonylphenol acrylate, propoxylated nonylphenol acrylate, 2-ethylhexyl carbitol acrylate, ω-carboxy-polycaprolactone monoacrylate, and 2-(2-ethoxyethoxy)ethyl acrylate. In addition, one or more of these may be used in combination. Acrylic acid and methacrylic acid will be referred to as (meth)acrylic acid, and acrylate and methacrylate will be referred to as (meth)acrylate.

[0026] Among these, (meth)acrylic acid esters having 1 to 20 carbon atoms in the ester moiety are preferably used, and (meth)acrylic acid alkyl esters having 1 to 20 carbon atoms in the ester moiety are more preferred, with methyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, and the like being particularly preferred.

[0027] In the present invention, commercially available products can be used as the moisture-curable resin (A). Examples of such products include EXESTAR ES2410, EXESTAR ES2420, and EXESTAR ES3430 manufactured by AGC Corporation, and MS POLYMER S-202, MS POLYMER S-203, MS POLYMER S-303, MS POLYMER S-903, MS POLYMER MAX-903, MS POLYMER MAX-901, MS POLYMER SAX-350, MS POLYMER SAT-200, MS POLYMER SAT-350, and MS POLYMER SAT-010 manufactured by Kaneka Corporation.

[0028] <Modified polyolefin resin (B)> The modified polyolefin resin (B) used in the present invention is a resin having a polyolefin modified by a functional group as the main skeleton, and is preferably a polyolefin resin having a structure similar to that of the main skeleton of the moisture-curable resin (A). Although not limited, it is more preferable that at least one of polyolefins such as polyethylene, polypropylene, and propylene-α-olefin copolymer is modified. Examples of the propylene-α-olefin copolymer include random copolymers, block copolymers, and graft copolymers. The modified polyolefin resin (B) preferably has a polyether structure or a (meth)acrylate structure, and is more preferably copolymerized with a polyether compound or a (meth)acrylate compound. Examples of the copolymerization include random copolymerization, block copolymerization, and graft copolymerization, and it is more preferable that the modified polyolefin resin is a polyolefin resin to which a polyether chain or a (meth)acrylate chain is grafted.

[0029] When the modified polyolefin resin (B) is a resin having the same polyether resin or (meth)acrylate polymer grafted to the main chain of the moisture-curable resin (A), the dispersibility and compatibility with the moisture-curable resin (A) are increased, and the blending ratio of the modified polyolefin resin (B) can be increased, resulting in a moisture-curable adhesive composition that has both excellent adhesion to polyolefin substrates and good liquidity. A good liquidity refers to a state in which the resin composition containing the moisture-curable resin (A) and the modified polyolefin resin (B) is a liquid that is not solid or gel-like, does not separate, or does not partially settle.

[0030] The polyether chain has the general formula -R 5 -O-(wherein, R 5 is a straight-chain or branched alkylene group having 1 to 15 carbon atoms. 5 is more preferably a linear or branched alkylene group having 2 to 8 carbon atoms, and further preferably a linear or branched alkylene group having 2 to 4 carbon atoms.

[0031] The method of grafting the polyether chain of the modified polyolefin resin (B) is not limited, but it is preferable to graft the polyolefin resin with a compound containing a functional group (1) such as an acidic group by reacting it with a radical generator, and then to react with a polyether resin having a functional group (2) such as an amino group or a hydroxyl group at one end, thereby grafting the polyether resin with a bonding mode such as an amide bond or an ester bond. The compound containing the functional group (1) is preferably at least one of compounds containing an acidic group such as α,β-unsaturated carboxylic acid and its acid anhydride, or at least one of monomers having an epoxy group. The functional group (2) is a functional group that reacts with the functional group (1), and is preferably an amino group or a hydroxyl group.

[0032] The method for grafting the (meth)acrylate chain of the modified polyolefin resin (B) is not limited, but it is preferable to graft-bond the polyolefin resin with a compound having a functional group (3) such as an acidic group by reacting it with a radical generator, and then to further react with a (meth)acrylate polymer having a functional group (4) such as an amino group or a hydroxyl group at one end, which reacts with the functional group (3), to graft-bond the polyolefin resin with an amide bond or an ester bond. The compound having the functional group (3) is preferably at least one of compounds containing an acidic group such as α,β-unsaturated carboxylic acid and its acid anhydride, or at least one of monomers having an epoxy group. The functional group (4) is a functional group that reacts with the functional group (3), and is preferably an amino group or a hydroxyl group.

[0033] The propylene-α-olefin copolymer is a copolymer of propylene as a main component with an α-olefin. As the α-olefin, for example, one or more of ethylene, 1-butene, 1-heptene, 1-octene, 4-methyl-1-pentene, vinyl acetate, etc. can be used. Among these α-olefins, ethylene and 1-butene are preferred. The ratio of the propylene component to the α-olefin component in the propylene-α-olefin copolymer is not limited, but the propylene component is preferably 50 mol% or more, more preferably 70 mol% or more.

[0034] The polypropylene random copolymer can be produced by a known method, for example, according to the production method described in JP-A-2001-206914, by charging propylene and olefins having 2 or more carbon atoms into a reaction vessel and continuously producing the copolymer while supplying hydrogen. The polymerization method can be carried out by known continuous polymerization such as bulk polymerization or gas phase polymerization, and is preferably carried out by one or multiple bulk polymerization stages.

[0035] Examples of the at least one α,β-unsaturated carboxylic acid and its acid anhydride include maleic acid, itaconic acid, citraconic acid, and their acid anhydrides. Among these, the acid anhydrides are preferred, and maleic anhydride is more preferred.

[0036] Examples of the monomer having an epoxy group include glycidyl (meth)acrylate, 4-hydroxybutyl acrylate glycidyl ether, and allyl glycidyl ether.

[0037] The radical generator can be used as a polymerization initiator. Examples of the radical generator include peroxides such as di-tert-butyl peroxyphthalate, tert-butyl hydroperoxide, dicumyl peroxide, benzoyl peroxide, tert-butyl peroxybenzoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, methyl ethyl ketone peroxide, di-tert-butyl peroxide, and lauroyl peroxide, and azonitriles such as azobisisobutyronitrile and azobisisopropionitrile.

[0038] In producing the modified polyolefin resin (B), the acid value of the resin grafted with at least one of α,β-unsaturated carboxylic acid and its acid anhydride as the functional group (1) used for grafting the polyether chain or (meth)acrylate chain is preferably 5 mg KOH / g-resin or more in terms of dispersibility and compatibility with the moisture-curing resin (A) and the liquid state of the resulting adhesive composition and adhesion to the polyolefin substrate, more preferably 7 mg KOH / g-resin or more, even more preferably 9 mg KOH / g-resin or more, even more preferably 11 mg KOH / g-resin or more, particularly preferably 13 mg KOH / g-resin or more, and most preferably 15 mg KOH / g-resin or more. By being 5 mg KOH / g-resin or more, the dispersibility and compatibility with the moisture-curing resin (A) are improved, the liquid state of the resulting adhesive composition is improved, and as a result, the adhesion to the polyolefin substrate tends to be improved. The upper limit is preferably 50 mgKOH / g-resin or less, more preferably 48 mgKOH / g-resin or less, even more preferably 46 mgKOH / g-resin or less, even more preferably 44 mgKOH / g-resin or less, particularly preferably 42 mgKOH / g-resin or less, and most preferably 40 mgKOH / g-resin or less. At 50 mgKOH / g-resin or less, the adhesion to polyolefin substrates tends to be good. This is also preferable from the viewpoint of production efficiency.

[0039] In producing the modified polyolefin resin (B), the epoxy equivalent of the resin grafted with at least one monomer having an epoxy group as the functional group (1) used for grafting the polyether chain or (meth)acrylate chain is preferably 30,000 g / eq. or less in terms of dispersibility and compatibility with the moisture-curing resin (A) and the liquid state of the resulting adhesive composition and adhesion to a polyolefin substrate, more preferably 25,000 g / eq. or less, even more preferably 20,000 g / eq. or less, even more preferably 15,000 g / eq. or less, particularly preferably 12,000 g / eq. or less, and most preferably 10,000 g / eq. or less. If it is 30,000 g / eq. or less, the dispersibility and compatibility with the moisture-curing resin (A) will be good, so the liquid state of the resulting adhesive composition will be good, and it tends to be practically usable as an adhesive. The lower limit is preferably 1,000 g / eq. or more, more preferably 1,100 g / eq. or more, even more preferably 1,200 g / eq. or more, even more preferably 1,300 g / eq. or more, particularly preferably 1,400 g / eq. or more, and most preferably 1,500 g / eq. or more. At 1,000 g / eq. or more, the adhesion to polyolefin substrates tends to be good. This is also preferable from the viewpoint of production efficiency.

[0040] The melting point (Tm) of the modified polyolefin resin (B) is preferably 100 ° C or less, more preferably 90 ° C or less, even more preferably 80 ° C or less, and most preferably 70 ° C or less, from the viewpoint of the liquid state of the moisture-curable adhesive composition. If it is 100 ° C or less, the viscosity of the moisture-curable adhesive composition does not increase significantly, or the fluidity is lost at room temperature and it is difficult to gel, so that the liquid state can be maintained within a range that can be substantially used as an adhesive. From the viewpoint of adhesive strength to a polyolefin substrate, the lower limit is preferably 30 ° C or more, more preferably 35 ° C or more, even more preferably 40 ° C or more, and most preferably 45 ° C or more. If it is 30 ° C or more, the cohesive force of the modified polyolefin resin (B) tends to be large and the adhesive strength tends to be good.

[0041] The weight average molecular weight (Mw) of the modified polyolefin resin (B) is preferably 150,000 or less, more preferably 130,000 or less, even more preferably 110,000 or less, and most preferably 90,000 or less, from the viewpoint of the liquid state of the moisture-curable adhesive composition. If it is 150,000 or less, the viscosity of the moisture-curable adhesive composition is unlikely to increase significantly, or the fluidity is unlikely to disappear at room temperature and gel, and the liquid state tends to be maintained within a range that can be substantially used as an adhesive. From the viewpoint of adhesive strength to a polyolefin substrate, the lower limit is preferably 10,000 or more, more preferably 20,000 or more, even more preferably 30,000 or more, and most preferably 40,000 or more. If it is 10,000 or more, the cohesive force of the modified polyolefin resin (B) tends to be large and the adhesive strength tends to be good.

[0042] The graft amount of the polyether resin and the (meth)acrylate polymer of the modified polyolefin resin (B) is preferably 40% by mass or less, more preferably 37% by mass or less, even more preferably 34% by mass or less, and most preferably 30% by mass or less, from the viewpoint of adhesion to a polyolefin substrate. If it is 40% by mass or less, the adhesion to a polyolefin substrate tends to be good. Furthermore, it is preferable because the production efficiency is also improved. The lower limit is preferably 2% by mass or more, more preferably 5% by mass or more, even more preferably 8% by mass or more, and most preferably 10% by mass or more, from the viewpoint of dispersibility and compatibility with the moisture-curing resin (A) and the liquid state of the adhesive composition obtained. If it is 2% by mass or more, the dispersibility and compatibility with the moisture-curing resin (A) are good, the liquid state of the adhesive composition obtained is good, and as a result, the adhesion to a polyolefin substrate tends to be improved.

[0043] The polyether resin having an amino group as the functional group (2) at one end is preferably, but not limited to, a primary amino group at one end, and more preferably has an ether bond such as polyethylene glycol, polypropylene glycol, polybutylene glycol, or polytetramethylene glycol.

[0044] The number average molecular weight of the polyether resin is preferably 10,000 or less in terms of reactivity with polyolefin having functional group (1), dispersibility and compatibility of the resulting modified polyolefin resin (B) and moisture-curable resin (A), and adhesion to polyolefin substrates, more preferably 7,000 or less, even more preferably 5,000 or less, particularly preferably 3,500 or less, and most preferably 2,500 or less. If it is 10,000 or less, the reactivity with the compound polyolefin having functional group (1) is improved, and as a result, the dispersibility and compatibility with the moisture-curable resin (A) are improved, and the ratio of the modified polyolefin resin (B) can be increased, and the adhesion to polyolefin substrates may be good. The lower limit is preferably 500 or more, more preferably 1,000 or more, particularly preferably 1,200 or more, and most preferably 1,500 or more. When it is 500 or more, the effect of improving dispersibility and compatibility due to grafting is good, and as a result, the dispersibility and compatibility with the moisture-curable resin (A) are improved, and the content ratio of the modified polyolefin resin (B) in the adhesive composition can be increased, which may result in good adhesion to polyolefin substrates.

[0045] The number average molecular weight of the (meth)acrylate polymer having the functional group (2) is preferably 10,000 or less in terms of reactivity with the polyolefin having the functional group (1), dispersibility and compatibility of the resulting modified polyolefin resin (B) and moisture-curable resin (A), and adhesion to the polyolefin substrate, more preferably 7,000 or less, even more preferably 5,000 or less, particularly preferably 3,500 or less, and most preferably 2,500 or less. If it is above the above range, the reactivity with the polyolefin having the functional group (1) decreases, and as a result, the dispersibility and compatibility with the moisture-curable resin (A) decreases, the ratio of the modified polyolefin resin (B) cannot be increased, and the adhesion to the polyolefin substrate may be reduced. The lower limit is preferably 500 or more, more preferably 1,000 or more, particularly preferably 1,200 or more, and most preferably 1,500 or more. If the amount is less than the above range, the effect of improving dispersibility and compatibility due to the grafting is reduced, resulting in reduced dispersibility and compatibility with the moisture-curable resin (A). As a result, it is not possible to increase the content ratio of the modified polyolefin resin (B) in the adhesive composition, and the adhesion to polyolefin substrates may be reduced.

[0046] The modified polyolefin resin (B) may be chlorinated. By being chlorinated, the compatibility with the moisture-curable resin (A) and the liquid state are further improved. When chlorinated, the chlorine content is usually 10 to 40 mass%.

[0047] The amount of modified polyolefin resin (B) relative to 100 parts by mass of moisture-curable resin (A) must be 2 parts by mass or more, preferably 5 parts by mass or more, more preferably 7 parts by mass or more, and most preferably 11 parts by mass or more, from the viewpoint of the liquid state of the adhesive composition and the adhesiveness to the polyolefin substrate. Also, it is preferably 100 parts by mass or less, more preferably 67 parts by mass or less, even more preferably 43 parts by mass or less, and most preferably 25 parts by mass or less. When the content of modified polyolefin resin (B) is 100 parts by mass or less relative to 100 parts by mass of moisture-curable resin (A), the adhesive composition tends to have a good liquid state. When the ratio of modified polyolefin resin (B) to moisture-curable resin (A) is 2 parts by mass or more, the adhesiveness to the polyolefin substrate tends to be good.

[0048] <Radical polymerizable monomer (C)> The radical polymerizable monomer (C) used in the present invention is not limited, but may be an acrylic monomer, a styrene monomer, a vinyl monomer, an unsaturated polyester monomer, or the like. Of these, an acrylic monomer is preferred because of its photocurability and the wide range of material options.

[0049] By blending a radically polymerizable monomer (C) with a moisture-curable adhesive composition and carrying out radical polymerization, heat of polymerization is generated and can be utilized to melt the modified polyolefin resin (B). As a result, an adhesive composition having superior wettability and adhesion to the substrate is obtained in the process of applying the adhesive composition to a polyolefin substrate and then curing the composition.

[0050] Examples of the acrylic monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, tridecyl (meth)acrylate, behenyl (meth)acrylate, and methoxyethyl (meth)acrylate. ) acrylate, ethoxyethyl (meth)acrylate, propoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxytetraethylene (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxytetraethylene glycol (meth)acrylate, phenoxyhexaethylene glycol (meth)acrylate, Methoxydipropylene glycol (meth)acrylate, methoxytripropylene glycol (meth)acrylate, cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, bornyl (meth)acrylate, isobornyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, allyl (meth)acrylate acrylate, allyl (meth)acrylate, 2-hydroxy-3-acryloyloxypropyl methacrylate, polyethylene glycol diacrylate, propoxylated ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A diacrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, propoxylated bisphenol A diacrylate, tricyclodecane dimethanol diacrylate, 1,10-decanediol diacrylate, 1,6-hexanediol diacrylate, 1,Examples of the diacrylate include 9-nonanediol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, polypropylene glycol diacrylate, and polytetramethylene glycol diacrylate. From the viewpoints of curability and compatibility with the modified polyolefin resin (B), polypropylene glycol diacrylate is preferred.

[0051] In the present invention, the radical polymerizable monomer (C) is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more, based on 100 parts by mass of the total of the moisture-curable resin (A) and the modified polyolefin resin (B). Also, it is preferably 200 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 50 parts by mass or less. By being in the range of 5 parts by mass or more and 200 parts by mass or less, both the liquid state and the adhesiveness to the polyolefin substrate tend to be good.

[0052] <Radical polymerization initiator (D)> The radical polymerization initiator (D) used in the present invention generates radicals and is an initiator for polymerization of the radically polymerizable monomer (C). Examples of the radical polymerization initiator (D) include, but are not limited to, a photopolymerization initiator that generates radicals upon irradiation with light, a thermal polymerization initiator that generates radicals upon heating, and a redox initiator. It is more preferable to use a photopolymerization initiator or a redox initiator that can initiate polymerization of the radically polymerizable monomer (C) without heating.

[0053] The photopolymerization initiator includes, but is not limited to, benzoin, benzophenone, acetophenone, acylphosphine oxide, thioxanthone, metallocene, quinone, etc., and specifically, known ones can be used. For example, benzophenone, 4-phenylbenzophenone, benzoylbenzoic acid, 2,2-diethoxyacetophenone, bisdiethylaminobenzophenone, benzyl benzoin, benzoyl isopropyl ether, benzyl dimethyl ketal, 1-hydroxycyclohexyl phenyl ketone, thioxanthone, 1-(4-isopropylphenyl)2-hydroxy-2-methylpropan-1-one, 1-(4-(2-hydroxyethoxy)-phenyl)-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy -2-methyl-1-phenylpropan-1-one, camphorquinone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2-methyl-1-(4-(methylthio)phenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone-1, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, and the like.

[0054] The above-mentioned redox (oxidation-reduction) initiators can be used in a wide temperature range. In particular, the following initiator types are advantageous in that they can be used at room temperature. Suitable redox initiators include, but are not limited to, combinations of inorganic peroxide initiators (persulfate initiators such as sodium persulfate, potassium persulfate, and ammonium persulfate) and inorganic reducing agents (sodium metabisulfite, sodium bisulfite, etc.); combinations of organic peroxides and tertiary amines, such as benzoyl peroxide / dimethylaniline, cumene hydroperoxide / dimethylaniline, and cumene hydroperoxide / condensates of butyraldehyde and aniline; and combinations of organic peroxides and transition metals. Preferred examples of the combinations include combinations of transition metals and tertiary amines, such as cumene hydroperoxide / cobalt naphthate, cumene hydroperoxide / copper naphthate, t-butyl hydroperoxide / cobalt naphthate, t-butyl hydroperoxide / copper naphthate, other hydroperoxides / other metal soaps, and the like; and combinations of transition metals and tertiary amines, such as copper naphthate / condensates of butyraldehyde and aniline, and other metal soaps / condensates of butyraldehyde and aniline, and the like. Examples of the other hydroperoxides include diisopropyl hydroperoxide, di-t-butyl peroxide, dicumyl peroxide, t-butyl peroxylaurate, t-butyl peroxydecanoate, t-butyl peroxybenzoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, p-methane hydroperoxide, diisopropylbenzene hydroperoxide, benzoyl peroxide, and methyl ethyl ketone peroxide. Examples of the other metal soaps include manganese naphthate, cobalt octoate, aluminum stearate, calcium stearate, zinc stearate, magnesium stearate, potassium oleate, and magnesium palmitate. From the viewpoint of curability and storage stability, a combination of an organic peroxide and a tertiary amine, and a combination of an organic peroxide and a transition metal are more preferable.

[0055] In the present invention, the radical polymerization initiator (D) is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and even more preferably 0.5 parts by mass or more, based on 100 parts by mass of the radical polymerizable monomer (C). Also, it is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less. By being in the range of 0.1 parts by mass or more and 5 parts by mass or less, both the liquid state and the adhesiveness to the polyolefin substrate tend to be good.

[0056] <Silanol condensation catalyst (E)> The silanol condensation catalyst (E) used in the present invention is used to cure the moisture-curable resin (A). Specifically, the silanol condensation catalyst (E) is used to promote a polycondensation reaction between silanol groups generated by hydrolysis of the hydrolyzable silyl groups of the moisture-curable resin (A) by moisture in the air, thereby obtaining a cured resin.

[0057] The silanol condensation catalyst (E) used in the present invention can be a wide variety of known silanol condensation catalysts. Specific examples thereof include titanate esters such as tetrabutyl titanate and tetrapropyl titanate, tin carboxylates such as dibutyltin dilaurate, dibutyltin maleate, dibutyltin diacetate, tin octylate, and tin naphthenate, thio-based tin compounds such as dibutyltin bisisononyl 3-mercaptopropionate and dibutyltin bisisooctylthioglycolate, reaction products of dibutyltin oxide and phthalate esters, organic aluminum compounds such as dibutyltin diacetylacetonate, aluminum trisacetylacetonate, aluminum trisethylacetoacetate, and diisopropoxyaluminum ethylacetoacetate, chelate compounds such as zirconium tetraacetylacetonate and titanium tetraacetylacetonate, and thio-based tin compounds such as dibutyltin diacetylacetonate, aluminum trisethylacetoacetate, and diisopropoxyaluminum ethylacetoacetate. Examples of the silanol condensation catalyst include amine compounds such as lead octylate, butylamine, octylamine, dibutylamine, monoethanolamine, diethanolamine, triethanolamine, diethylenetriamine, triethylenetetramine, oleylamine, cyclohexylamine, benzylamine, diethylaminopropylamine, xylylenediamine, triethylenediamine, guanidine, diphenylguanidine, 2,4,6-tris(dimethylaminomethyl)phenol, morpholine, N-methylmorpholine, 2-ethyl-4-methylimidazole, and 1,8-diazabicyclo(5,4,0)undecene-7 (DBU), as well as salts of these amine compounds with carboxylic acids, and further include other known silanol condensation catalysts such as acid catalysts and basic catalysts. These catalysts may be used alone or in combination of two or more.

[0058] In the present invention, the silanol condensation catalyst (E) is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and even more preferably 0.5 parts by mass or more, based on 100 parts by mass of the moisture-curable resin (A). Also, it is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less. By being in the range of 0.1 parts by mass or more and 5 parts by mass or less, both the liquid state and the adhesion to the polyolefin substrate tend to be good.

[0059] <Moisture-curable adhesive composition> The moisture-curable adhesive composition according to the present invention is cured by hydrolysis of hydrolyzable silyl groups by atmospheric moisture, and condensation polymerization of the resulting silanol groups. Therefore, when used as a one-liquid composition, it is handled in an airtight sealed state during storage or transportation so as not to come into contact with air (moisture in the air). When used, it is opened and applied to any desired location, and it comes into contact with moisture in the air and reacts to cure. When used as a two-liquid moisture-curable adhesive composition, at least the composition consisting of the moisture-curable resin (A), modified polyolefin resin (B), radical polymerizable monomer (C), and radical polymerization initiator (D), and the silanol condensation catalyst (E) are supplied separately, and by mixing them at the time of use, the above-mentioned moisture curing reaction proceeds and the adhesive cures.

[0060] The moisture-curable composition of the present invention has excellent adhesion to polyolefin substrates, but also exhibits good adhesion to many other substrates, such as metals, glass, and painted surfaces, and can be used as an adhesive, joint material, sealant, waterproofing material, paint / coating material, lining material, sealant, adhesive tape, adhesive sheet, pressure-sensitive adhesive, adhesive processed product, etc.

[0061] <Other additives> In addition to the above-mentioned moisture-curable resin (A), modified polyolefin resin (B), radically polymerizable monomer (C), radical polymerization initiator (D), and silanol condensation catalyst (E), the adhesive composition of the present invention may contain various additives, such as plasticizers, organic solvents, tackifiers, adhesion promoters, fillers, stabilizers, waxes, antioxidants, UV absorbers, light stabilizers, thixotropes, colorants, and antiblocking agents, as necessary, in order to adjust viscosity and physical properties, so long as the additives do not impair the performance of the present invention.

[0062] The plasticizer is not particularly limited, and various plasticizers can be used, including hydrocarbons such as process oils and various alkanes, as well as phthalates, polyalkylene glycol esters, and phosphates. Examples of the plasticizer include phthalates such as dioctyl phthalate, dibutyl phthalate, diheptyl phthalate, di(2-ethylhexyl) phthalate, butyl benzyl phthalate, butyl phthalyl butyl glycolate, and diisononyl phthalate; non-aromatic dibasic acid esters such as dioctyl adipate and dioctyl sebacate; polyalkylene glycol esters such as diethylene glycol dibenzoate and triethylene glycol dibenzoate; phosphate esters such as tricresyl phosphate and tributyl phosphate; acrylic polymers; chlorinated paraffins; alkyl diphenyls; hydrocarbon oils such as partially hydrogenated terphenyls; process oils; and alkyl benzenes.

[0063] The organic solvent is not particularly limited, but is preferably one which dissolves the moisture-curable resin (A) and the modified polyolefin resin (B). Examples of the organic solvent include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as hexane, heptane, octane, and decane; alicyclic hydrocarbons such as cyclohexane, cyclohexene, methylcyclohexane, and ethylcyclohexane; halogenated hydrocarbons such as trichloroethylene, dichloroethylene, chlorobenzene, and chloroform; methanol, ethanol, isopropyl alcohol, butanol, pentachloroethane, and the like. alcohol-based solvents such as ethanol, 1-hexanol, 2-ethylhexanol, 2-methylcyclohexanol, propanediol, phenol, 2-heptyl alcohol, etc.; ketone-based solvents such as acetone, methyl isobutyl ketone, methyl ethyl ketone, pentanone, hexanone, cyclohexanone, isophorone, acetophenone, etc.; cellosolves such as methyl cellosolve, ethyl cellosolve, etc.; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, methyl propionate, ethyl propionate, butyl formate, etc.; Examples of organic solvents include ether-based solvents such as ethylene glycol mono-iso-butyl ether, ethylene glycol mono-tert-butyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol mono-iso-butyl ether, triethylene glycol mono-n-butyl ether, tetraethylene glycol mono-n-butyl ether, dibenzyl ether, diphenyl ether and butylphenyl ether. The incorporation of a small amount of an organic solvent is preferred because it further reduces the viscosity of the moisture-curable adhesive composition, improving its liquid state and coatability when used.

[0064] Examples of tackifiers include, but are not limited to, styrene copolymer resins, terpene resins, petroleum resins (e.g., C5 hydrocarbon resins, C9 hydrocarbon resins, C5-C9 hydrocarbon copolymer resins, and hydrogenated resins thereof), rosin ester resins and hydrogenated resins thereof, phenolic resins, modified phenolic resins (e.g., cashew oil modified phenolic resins, rosin phenolic resins, polymerized rosin, polymerized rosin esters, tall oil modified phenolic resins, and the like), terpene phenolic resins, xylene-phenolic resins, cyclopentadiene-phenolic resins, coumarone-indene resins, DCPD resins, xylene resins, low molecular weight polystyrene resins, and the like. The incorporation of a tackifier is preferred because it imparts appropriate adhesion to the cured product of the moisture-curable adhesive composition of the present invention and improves adhesion to polyolefin substrates.

[0065] The adhesion promoter is not particularly limited, but examples thereof include a silane coupling agent, and the like. By incorporating an adhesion promoter, it is possible to improve adhesion to many substrates such as polyolefin substrates, metals, glass, and painted surfaces, and thus it is preferable.

[0066] As the silane coupling agent serving as an adhesion promoter, an organosilane represented by the general formula (B) can be used. General formula (B) [ka] (In the formula, R 6 and R 7 are each a monovalent hydrocarbon group having 1 to 4 carbon atoms, Y is a monovalent hydrocarbon group which may contain a substituent or a substituent atom, a and b are each an integer of 0 to 2, and the sum of a and b is 0 to 2.

[0067] Examples of organosilanes represented by the general formula (B) include dimethyldimethoxysilane, methyltrimethoxysilane, tetramethoxysilane, dimethyldiethoxysilane, methyltriethoxysilane, tetraethoxysilane, diphenyldimethoxysilane, phenyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, aminomethyltriethoxysilane, N-β(aminoethyl)aminomethyltrimethoxysilane, N-β(aminoethyl)methyltributoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldieth ... Examples of the organosilanes include noisobutyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, {[N-β(aminoethyl)]N-β(aminoethyl)}γ-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, 3,4-epoxycyclohexylethyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-isocyanatepropyltrimethoxysilane, γ-isocyanatepropylmethyldiethoxysilane, etc. These organosilanes may be used alone or in combination of two or more. Among these, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, etc. are preferably selected because they have a high adhesiveness-imparting effect and are fast curing.

[0068] The mixing ratio of the adhesion imparting agent in the present invention is preferably 0 to 15 parts by mass, particularly preferably 1 to 10 parts by mass, based on 100 parts by mass of the total of the moisture-curable resin (A) and the modified polyolefin resin (B). The addition of the adhesion imparting agent effectively acts as a crosslinking agent, and the moisture-curable composition is easily cured quickly. When the amount is 15 parts by mass or less, the adhesion imparting effect is large and the composition is easily cured quickly.

[0069] The filler is not particularly limited, but examples thereof include calcium carbonate, carbon black, clay, talc, titanium oxide, quicklime, kaolin, zeolite, diatomaceous earth, glass balloons, etc., which can be used alone or in combination. Among these, calcium carbonate is preferred as the filler, since it is easy to obtain a well-balanced combination of various properties, such as the viscosity of the moisture-curable composition of the present invention and the rigidity and heat resistance of the cured product.

[0070] <About the substrate to be adhered> Examples of polyolefin substrates that are adherend substrates include conventionally known high density polyethylene (HDPE), low density polyethylene (LDPE), very low density polyethylene (VLDPE), linear low density polyethylene (LLDPE), ultra-high molecular weight polyethylene (UHMW-PE), isotactic polypropylene, syndiotactic polypropylene, atactic polypropylene, block copolymers of ethylene and propylene, random copolymers (copolymers with ethylene, binary copolymers with butene-1, and terpolymers (terpolymers) with ethylene / butene-1). Examples of heterogeneous substrates include polyester resins such as polyethylene terephthalate, polycarbonate resins, polyamide resins such as nylon 6, resins such as acrylonitrile butadiene styrene copolymers, and vinyl chloride resins, and metals such as iron, stainless steel, aluminum, cold-rolled steel, and magnesium alloys. The moisture-curable adhesive composition of the present invention is used to bond these polyolefin substrates to each other or to these polyolefin substrates and these heterogeneous substrates.

[0071] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the examples. In the examples and comparative examples, parts simply indicate parts by mass.

[0072] [Production Example 1] In a 1L autoclave, 100 parts by mass of a propylene polymer (Idemitsu Kosan Co., Ltd.'s "Elmodu (registered trademark) S600"), 150 parts by mass of toluene, 2 parts by mass of maleic anhydride, and 10 parts by mass of di-tert-butyl peroxide were added, and the temperature was raised to 160 ° C., followed by stirring for another 3 hours. After that, the resulting reaction liquid was cooled and poured into a container containing a large amount of methyl ethyl ketone to precipitate a resin. Then, the liquid containing the resin was centrifuged to separate and purify the acid-modified propylene polymer in which maleic anhydride was graft-polymerized, (poly)maleic anhydride, and low molecular weight substances. Then, the mixture was dried under reduced pressure at 50 ° C. for 5 hours to obtain a maleic anhydride-modified propylene polymer (MPO-1, acid value 4 mg KOH / g-resin, weight average molecular weight 29,000).

[0073] [Production Example 2 ] In a 1L autoclave, 100 parts by mass of a propylene-butene copolymer ("Tafmer (registered trademark) XM7070" manufactured by Mitsui Chemicals, Inc., propylene / 1-butene = 75 / 25 (molar ratio)), 150 parts by mass of toluene, 2 parts by mass of maleic anhydride, and 0.5 parts by mass of tert-butylperoxyisopropyl monocarbonate were added, and the mixture was heated to 120°C and further stirred for 1 hour. Thereafter, in the same manner as in Production Example 1, a maleic anhydride-modified propylene-butene copolymer (MPO-2, acid value 4 mg KOH / g-resin, weight average molecular weight 109,000) was obtained.

[0074] [Production Example 3] A maleic anhydride-modified propylene polymer (MPO-3, acid value 25 mg KOH / g-resin, weight average molecular weight 26,000) was obtained in the same manner as in Production Example 1, except that the amount of maleic anhydride added was 20 parts by mass.

[0075] [Production Example 4] A maleic anhydride-modified propylene-butene copolymer (MPO-4, acid value 25 mg KOH / g-resin, weight average molecular weight 116,000) was obtained by the same procedure as in Production Example 2, except that the amount of maleic anhydride charged was 20 parts by mass and the amount of tert-butylperoxyisopropyl monocarbonate charged was 2 parts by mass.

[0076] [Production Example 5] In a 1 L autoclave, 100 parts by mass of a propylene-butene copolymer ("Tafmer (registered trademark) XM7070" manufactured by Mitsui Chemicals, Inc.), 150 parts by mass of toluene, 18 parts by mass of maleic anhydride, and 6 parts by mass of di-tert-butyl peroxide were added, and the mixture was heated to 160° C. and further stirred for 3 hours. Thereafter, the same procedure as in Production Example 1 was followed to obtain a maleic anhydride-modified propylene-butene copolymer (MPO-5, acid value 17 mg KOH / g-resin, weight average molecular weight 58,000).

[0077] [Production Example 6] 100 parts by mass of propylene-butene copolymer ("Tafmer (registered trademark) XM7070" manufactured by Mitsui Chemicals, Inc.), 150 parts by mass of toluene, 7 parts by mass of maleic anhydride, and 6 parts by mass of tert-butylperoxyisopropyl monocarbonate were added to a 1 L autoclave, and the mixture was heated to 140° C. and further stirred for 3 hours. Thereafter, the same procedure as in Production Example 1 was followed to obtain a maleic anhydride-modified propylene-butene copolymer (MPO-6, acid value 7 mg KOH / g-resin, weight average molecular weight 84,000).

[0078] [Production Example 7] In a 1 L autoclave, 100 parts by mass of a propylene-butene copolymer ("Tafmer (registered trademark) XM7070" manufactured by Mitsui Chemicals, Inc.), 150 parts by mass of toluene, 7 parts by mass of maleic anhydride, and 6 parts by mass of di-tert-butyl peroxide were added, and the mixture was heated to 160° C. and further stirred for 3 hours. Thereafter, the same procedure as in Production Example 1 was carried out to obtain a maleic anhydride-modified propylene-butene copolymer (MPO-7, acid value 19 mg KOH / g-resin, weight average molecular weight 44,000).

[0079] [Production Example 8] A maleic anhydride-modified propylene-butene copolymer (MPO-8, acid value 26 mg KOH / g-resin, weight average molecular weight 40,000) was obtained by the same procedure as in Production Example 5, except that the amount of maleic anhydride charged was 25 parts by mass and the amount of di-tert-butyl peroxide charged was 10 parts by mass.

[0080] [Production Example 9] In a 1L autoclave, 100 parts by mass of a propylene-butene copolymer ("Tafmer (registered trademark) XM7080" manufactured by Mitsui Chemicals, Inc., propylene / 1-butene = 80 / 20 (molar ratio)), 150 parts by mass of toluene, 1 part by mass of maleic anhydride, and 0.5 parts by mass of tert-butylperoxyisopropyl monocarbonate were added, and the mixture was heated to 140°C and further stirred for 3 hours. Thereafter, in the same manner as in Production Example 1, a maleic anhydride-modified propylene polymer (MPO-9, acid value 2 mg KOH / g-resin, weight average molecular weight 170,000) was obtained.

[0081] [Production Example 10] In a 1 L autoclave, 100 parts by mass of a propylene polymer (Idemitsu Kosan Co., Ltd.'s "ELMODU (registered trademark) S600"), 150 parts by mass of toluene, 12 parts by mass of glycidyl methacrylate, and 4 parts by mass of di-tert-butyl peroxide were added, and the mixture was heated to 140°C and further stirred for 3 hours. Thereafter, the same procedure as in Production Example 1 was carried out to obtain a glycidyl methacrylate-modified propylene polymer (GPO-1, epoxy equivalent 8,800 g / eq., weight average molecular weight 66,000).

[0082] [Production Example 11] A 500 ml four-neck flask equipped with a water-cooled reflux condenser and a stirrer was charged with 100 parts by mass of the maleic anhydride modified propylene polymer (MPO-1) obtained in Production Example 1 and 15 parts by mass of polyetheramine (manufactured by Huntsman, "Jeffamine (registered trademark) M-2000"), and the mixture was heated to 110°C with stirring. Stirring was continued for 3 hours, and then the mixture was cooled to obtain a polyether modified propylene polymer (PO-1, graft amount 6.1% by mass, weight average molecular weight 30,000, melting point 50°C).

[0083] [Production Example 12] A polyether-modified propylene-butene copolymer (PO-2, graft amount 6.0 mass%, weight average molecular weight 110,000, melting point 68°C) was obtained in the same manner as in Production Example 11, except that the maleic anhydride-modified propylene polymer (MPO-1) was changed to a maleic anhydride-modified propylene-butene copolymer (MPO-2).

[0084] [Production Example 13] A polyether-modified propylene polymer (PO-3, graft amount 37.1% by mass, weight average molecular weight 30,000, melting point 45° C.) was obtained in the same manner as in Production Example 11, except that the maleic anhydride-modified propylene polymer (MPO-1) was changed to a maleic anhydride-modified propylene polymer (MPO-3) and the amount of polyetheramine (manufactured by Huntsman, “Jeffamine (registered trademark) M-2000”) added was changed to 93 parts by mass.

[0085] [Production Example 14] A polyether-modified propylene-butene copolymer (PO-4, graft amount 37.0 mass%, weight average molecular weight 120,000, melting point 60°C) was obtained in the same manner as in Production Example 13, except that the maleic anhydride-modified propylene polymer (MPO-3) was changed to a maleic anhydride-modified propylene-butene copolymer (MPO-4).

[0086] [Production Example 15] A polyether-modified propylene-butene copolymer (PO-5, graft amount 22.9% by mass, weight average molecular weight 61,000, melting point 55°C) was obtained in the same manner as in Production Example 11, except that the maleic anhydride-modified propylene polymer (MPO-1) was replaced with a maleic anhydride-modified propylene-butene copolymer (MPO-5) and the amount of polyetheramine (Jeffamine (registered trademark) M-2000, manufactured by Huntsman) was changed to 63 parts by mass.

[0087] [Production Example 16] A polyether-modified propylene-butene copolymer (PO-6, graft amount 10.9 mass%, weight average molecular weight 85,000, melting point 65°C) was obtained in the same manner as in Production Example 11, except that the maleic anhydride-modified propylene polymer (MPO-1) was changed to a maleic anhydride-modified propylene-butene copolymer (MPO-6) and the amount of polyetheramine (manufactured by Huntsman, "Jeffamine (registered trademark) M-2000") added was changed to 27 parts by mass.

[0088] [Production Example 17] A polyether-modified propylene-butene copolymer (PO-7, graft amount 28.4 mass%, weight average molecular weight 47,000, melting point 47°C) was obtained in the same manner as in Production Example 11, except that the maleic anhydride-modified propylene polymer (MPO-1) was changed to a maleic anhydride-modified propylene-butene copolymer (MPO-7) and the amount of polyetheramine (manufactured by Huntsman, "Jeffamine (registered trademark) M-2000") added was changed to 72 parts by mass.

[0089] [Production Example 18] A polyether-modified propylene-butene copolymer (PO-8, graft amount 12.9% by mass, weight average molecular weight 41,000, melting point 35°C) was obtained in the same manner as in Production Example 11, except that the maleic anhydride-modified propylene polymer (MPO-1) was changed to a maleic anhydride-modified propylene-butene copolymer (MPO-8) and the polyetheramine (manufactured by Huntsman, "Jeffamine (registered trademark) M-2000") was changed to 29 parts by mass of polyetheramine (manufactured by Huntsman, "Jeffamine (registered trademark) M-600") instead of 15 parts by mass.

[0090] [Production Example 19] A polyether-modified propylene-butene copolymer (PO-9, graft amount 26.9% by mass, weight average molecular weight 60,000, melting point 55°C) was obtained in the same manner as in Production Example 11, except that the maleic anhydride-modified propylene polymer (MPO-1) was changed to a maleic anhydride-modified propylene-butene copolymer (MPO-5) and 15 parts by mass of polyetheramine (manufactured by Huntsman, "Jeffamine (registered trademark) M-2000") was changed to 98 parts by mass of polypropylene glycol monobutyl ether (manufactured by NOF Corporation, "UNILUB (registered trademark) MB-700").

[0091] [Manufacturing Example 20] An acrylic-modified propylene polymer (PO-10, graft amount 18.3% by mass, weight average molecular weight 60,000, melting point 56° C.) was obtained in the same manner as in Production Example 11, except that 15 parts by mass of polyetheramine (manufactured by Huntsman, “Jeffamine (registered trademark) M-2000”) was changed to 48 parts by mass of a hydroxyl group-containing acrylic polymer (manufactured by Soken Chemical & Engineering Co., Ltd., “Actflow (registered trademark) UMB-1001”).

[0092] [Production Example 21] A polyether-modified propylene polymer (PO-11, graft amount 28.0 mass%, weight average molecular weight 68,000, melting point 58°C) was obtained in the same manner as in Production Example 11, except that the maleic anhydride-modified propylene polymer (MPO-1) was replaced with a glycidyl methacrylate-modified propylene polymer (GPO-1) and the amount of polyetheramine (manufactured by Huntsman, "Jeffamine (registered trademark) M-2000") was changed to 47 parts by mass.

[0093] [Production Example 22] A polyether-modified propylene polymer (PO-12, graft amount 4.1 mass%, weight average molecular weight 172,000, melting point 75°C) was obtained in the same manner as in Production Example 11, except that the maleic anhydride-modified propylene polymer (MPO-1) was changed to a maleic anhydride-modified propylene-butene copolymer (MPO-9) and the amount of polyetheramine (manufactured by Huntsman, "Jeffamine (registered trademark) M-2000") was changed to 10 parts by mass.

[0094] [Preparation of main agent 1] A 500 ml four-neck flask equipped with a water-cooled reflux condenser and a stirrer was charged with 95 parts by mass of hydrolyzable silyl group-containing polyether resin A-1 and 5 parts by mass of the polyether-modified propylene polymer PO-1 obtained in Production Example 11, and the mixture was heated to 110°C with stirring. Stirring was continued for 1 hour, and then the mixture was cooled to below 40°C to obtain main agent 1.

[0095] [Preparation of base materials 2 to 16] The moisture-curing resin and modified polyolefin resin were changed as shown in Table 1, and in base agent 12, polypropylene glycol #700 diacrylate was added as a radical polymerizable monomer at the same time as the moisture-curing resin and modified polyolefin resin, and base agents 2 to 16 were prepared in the same manner as base agent 1. The blending amounts are shown in Table 1.

[0096] [Table 1]

[0097] [Example 1] An adhesive composition was obtained by mixing 100 parts by mass of the main component 1 obtained as described above with 1 part by mass of dibutyltin dilaurate as a silanol condensation catalyst. The liquid state and adhesion test results are shown in Table 2.

[0098] [Examples 2 to 15, Comparative Examples 1 to 3] The base materials 1 to 16 and dibutyltin dilaurate were changed as shown in Tables 2 and 3, and in Example 12, 1-hydroxycyclohexyl phenyl ketone, a radical polymerization initiator, was blended simultaneously with the base material and the silanol condensation catalyst, and Examples 2 to 15 and Comparative Examples 1 to 3 were carried out in the same manner as Example 1. The blending amounts, liquid state, and adhesive property test results are shown in Tables 2 and 3. However, Comparative Example 3 was poorly liquid and gelled, so it could not be evaluated as an adhesive.

[0099] [Table 2]

[0100] [Table 3]

[0101] [Materials used] The materials used in Tables 1, 2, and 3 are as follows: <Moisture-curing resin (A)> (A-1) A hydrolyzable silyl group-containing polyether resin having a number average molecular weight of 18,000, a viscosity at 25°C of 12,000 mPa s, and an average number of hydrolyzable silyl groups per molecule of 1.4 (A-2) A hydrolyzable silyl group-containing acrylic polymer (radical polymerizable monomer (C)) having a number average molecular weight of 9,000, a viscosity at 25°C of 7,000 mPa s, and an average number of hydrolyzable silyl groups per molecule of 1.0. (Polypropylene glycol diacrylate) Polypropylene glycol #700 diacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., NK Ester (registered trademark) APG-700) <Radical polymerization initiator (D)> (1-Hydroxycyclohexyl phenyl ketone) Reagent sold by Tokyo Chemical Industry Co., Ltd. <Silanol condensation catalyst (E)> (Dibutyltin dilaurate) Reagent sold by Tokyo Chemical Industry Co., Ltd.

[0102] The acid-modified polyolefin, glycidyl methacrylate-modified polyolefin, polyether resin-modified polyolefin, (meth)acrylate polymer polyolefin and adhesive composition obtained as described above were subjected to analytical measurements and evaluations according to the following methods.

[0103] Acid Number Measurement The acid value (mgKOH / g-resin) in the present invention is a value calculated by the following formula using an FT-IR (FT-IR8200PC, manufactured by Shimadzu Corporation) and the coefficient (f) obtained from a calibration curve prepared using a chloroform solution of maleic anhydride (manufactured by Tokyo Chemical Industry Co., Ltd.) and the absorbance (I) of the stretching peak (1780 cm-1) of the carbonyl (C=O) bond of maleic anhydride in a crystalline maleic anhydride-modified polyolefin solution. Acid value (mgKOH / g-resin) = [absorbance (I) x (f) x 2 x molecular weight of potassium hydroxide x 1000 (mg) / molecular weight of maleic anhydride] Molecular weight of maleic anhydride: 98.06 Molecular weight of potassium hydroxide: 56.11

[0104] Epoxy equivalent weight measurement The epoxy equivalent (g / eq.) in the present invention is a value calculated by the following formula using an FT-IR (FT-IR8200PC, manufactured by Shimadzu Corporation) with a coefficient (f) obtained from a calibration curve prepared from a chloroform solution of glycidyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) and the absorbance (I) of the stretching peak (1732 cm-1) of the ester carbonyl (C=O) bond of glycidyl methacrylate in a glycidyl methacrylate-modified polyolefin solution. Epoxy equivalent (g / eq.) = 100 / {[absorbance (I) × (f)] / molecular weight of glycidyl methacrylate} Molecular weight of glycidyl methacrylate: 142.15

[0105] Measurement of weight average molecular weight (Mw) The weight average molecular weight in the present invention is a value measured by gel permeation chromatography Alliance e2695 manufactured by Nippon Waters (hereinafter referred to as GPC, standard substance: polystyrene resin, mobile phase: tetrahydrofuran).

[0106] Melting point determination The melting point and heat of fusion in the present invention are values ​​measured using a differential scanning calorimeter (hereinafter, DSC, manufactured by TA Instruments Japan, Q-2000) from the top temperature and area of ​​the melting peak when the material is heated to melt at a rate of 20°C / min, cooled to resinify, and then heated to melt again.

[0107] Measurement of graft amount The graft amount in the present invention was determined by dissolving 100 g of the modified polyolefin resin in 250 g of toluene with heating, adding it to 1000 g of acetone, filtering the precipitate, and drying the resulting purified modified polyolefin resin. The graft amount (wt%) of the polyether resin and the acrylic polymer was determined by measuring the purified product with 1H-NMR (400 MHz, manufactured by Varian Inova).

[0108] Evaluation of liquid adhesive composition The liquid adhesive compositions shown in Tables 1 and 2 were evaluated by measuring the solution viscosity at 25° C. at a rotation speed of 0.5 rpm using a Toki Sangyo Co., Ltd. E-type viscometer TVE-22H and rotor No. 0.8°. <Evaluation criteria> ○ (Excellent for practical use): Less than 20 Pa·s △ (practical): 20 Pa·s or more and less than 30 Pa·s × (not practical): 30 Pa·s or more, gelation and separation / precipitation occur

[0109] Preparation of adhesive plates The substrates used were a PP plate whose surface had been purified with isopropyl alcohol, and an aluminum plate A1050P (both manufactured by Nippon Test Panel Co., Ltd., length x width x thickness = 100mm x 25mm x 2mm) that had been degreased by immersion in a degreasing solution (a 4 wt% solution of Fine Cleaner FC315E manufactured by Nippon Parkerizing Co., Ltd.) heated to 60°C for 5 minutes, then rinsed and wiped dry. Using a wire bar coater No. 16, the adhesive compositions obtained in each of the Examples and Comparative Examples, except for the adhesive composition obtained in Example 11, were applied to a PP plate, and then an aluminum plate A1050P of 25 mm x 20 mm was brought into contact with the plate and pressed at 25°C, 0.05 MPa, and for 10 seconds using a heat sill tester TP-701-B manufactured by Tester Sangyo Co., Ltd. The adhesive joint was then fixed with a clip (small double clip manufactured by Askul Co., Ltd., width 19 mm) and cured for 168 hours in an atmosphere of 25°C and 60% RH. Similarly, the adhesive composition obtained in Example 12 was applied to a PP plate using a wire bar coater No. 16, and then irradiated with ultraviolet light from a distance of 4 cm for 5 seconds using a Multilight ML-251A / B manufactured by Ushio Inc. Thereafter, similarly, an aluminum plate A1050P was brought into contact with the plate at 25 mm x 20 mm, and pressure-bonded at 25°C, 0.05 MPa, and 10 seconds using a Heat Sill Tester TP-701-B manufactured by Tester Sangyo Co., Ltd., and the adhesive portion was fixed with a clip (small double clip manufactured by Askul Co., Ltd., width 19 mm) and aged for 168 hours in an atmosphere of 25°C and 60% RH.

[0110] Adhesion Test The bonded plates were cured for 168 hours, and then subjected to a tensile test at a tensile speed of 50 mm / min using Tensilon RTM-100 manufactured by Orientec Corporation in an atmosphere of 25° C. to evaluate the tensile shear strength. <Evaluation criteria> ○ (Excellent for practical use): 1.0 MPa or more △ (practical): 0.2MPa or more and less than 1.0MPa × (not practical): Less than 0.2 MPa [Industrial Applicability]

[0111] The moisture-curable composition and adhesive of the present invention are capable of obtaining adhesive strength sufficient for practical use with poorly adhesive materials such as polyolefin materials, and further exhibit good adhesion to a variety of materials such as metals, glass and painted surfaces. Therefore, they can be practically used as adhesives, joint materials, sealants, waterproofing materials, paints and coatings, lining materials, sealing materials, adhesive tapes, adhesive sheets, pressure-sensitive adhesives, adhesive processed products and the like, and are extremely useful industrially.

Claims

1. Contains a moisture-curable resin (A) and a modified polyolefin resin (B), The content of the modified polyolefin resin (B) is 2 parts by mass or more relative to 100 parts by mass of the moisture-curable resin (A); The adhesive resin composition, wherein the modified polyolefin resin (B) has a polyether structure or a (meth)acrylate polymer structure.

2. The adhesive resin composition described in claim 1, wherein the moisture-curable resin (A) contains a hydrolyzable silyl group.

3. The adhesive resin composition described in claim 1 or 2, wherein the moisture-curable resin (A) is a resin containing a hydrolyzable silyl group at an end and having a main chain made of polyether or (meth)acrylate.

4. An adhesive resin composition described in any one of claims 1 to 3, wherein the modified polyolefin resin (B) is a resin having an amide bond and / or an ester bond.

5. An adhesive resin composition described in any one of claims 1 to 3, wherein the content of polyether resin or (meth)acrylate polymer in the modified polyolefin resin (B) is 2 to 40 mass %.

6. An adhesive resin composition described in any one of claims 1 to 5, wherein the modified polyolefin resin (B) has a weight average molecular weight of 10,000 to 150,000.

7. The adhesive resin composition according to any one of claims 1 to 6, further comprising a radical polymerizable monomer (C).

8. The adhesive resin composition according to claim 7, wherein the radical polymerizable monomer (C) is a compound containing a (meth)acryloyl group at an end.

9. The adhesive resin composition according to any one of claims 1 to 8, further comprising a radical polymerization initiator (D).

10. The adhesive resin composition according to any one of claims 1 to 9, further comprising a silanol condensation catalyst (E).

Citation Information

Patent Citations

  • Heat-accumulating material

    JP1984022985A

  • Modified polyolefin composition and its use

    JP2001139642A

  • Adhesive composition

    JP2016094566A

  • Curable composition

    WO2007142067A1

  • Adhesive composition for batteries and adhesive member for batteries using same

    WO2019142716A1